Transcriptome profiling identifies TIGIT as a marker of T-cell exhaustion in liver cancer - Ostroumov, Dmitrij; Duong, Steven; Wingerath, Jessica; Woller, Norman; Manns, Michael P.; Timrott, Kai; Kleine, Moritz; Ramackers, Wolf-Rüdiger; Rössler, Stephanie; Nahnsen, Sven; Dittrich-Breiholz, Oliver; Eggert, Tobias; et al. (Hepatology, 2021)
BACKGROUND AND AIMS Programmed death 1 (PD-1) checkpoint inhibition has shown promising results in patients with hepatocellular carcinoma, inducing objective responses in approximately 20% of treated patients. The roles of other coinhibitory molecules and their individual contributions to T-cell dysfunction in liver cancer, however, remain largely elusive. APPROACH AND RESULTS We performed a comprehensive mRNA profiling of cluster of differentiation 8 (CD8) T cells in a murine model of autochthonous liver cancer by comparing the transcriptome of naive, functional effector, and exhausted, tumor-specific CD8 T cells. Subsequently, we functionally validated the role of identified genes in T-cell exhaustion. Our results reveal a unique transcriptome signature of exhausted T cells and demonstrate that up-regulation of the inhibitory immune receptor T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibitor motif domains (TIGIT) represents a hallmark in the process of T-cell exhaustion in liver cancer. Compared to PD-1, expression of TIGIT more reliably identified exhausted CD8 T cells at different stages of their differentiation. In combination with PD-1 inhibition, targeting of TIGIT with antagonistic antibodies resulted in synergistic inhibition of liver cancer growth in immunocompetent mice. Finally, we demonstrate expression of TIGIT on tumor-infiltrating CD8 T cells in tissue samples of patients with hepatocellular carcinoma and intrahepatic cholangiocarcinoma and identify two subsets of patients based on differential expression of TIGIT on tumor-specific T cells. CONCLUSIONS Our transcriptome analysis provides a valuable resource for the identification of key pathways involved in T-cell exhaustion in patients with liver cancer and identifies TIGIT as a potential target in checkpoint combination therapies.
First published: 27 July 2020
Gesehen am 08.06.2021